Overexpression of long noncoding RNA LINC00638 inhibits inflammation and oxidative stress in rheumatoid arthritis fibroblast‐like synoviocytes by regulating the Nrf2/HO‐1 pathway. Issue 7 (20th June 2022) - Sun, Yanqiu; Liu, Jian; Wen, Jianting; Huang, Dan; Zhou, Qin; Zhang, Xianheng; Ding, Xiang; Chen, Xiaolu
Abstract: Background: Abnormal expression of long noncoding RNAs (lncRNAs) is involved in several autoimmune diseases including rheumatoid arthritis (RA). In this study, we intended to explore the expression of lncRNA LINC00638 in RA and its potential mechanism of action related to inflammation and oxidative stress. Methods: The level of LINC00638 in the peripheral blood mononuclear cells (PBMCs) obtained from 45 RA patients and 30 normal controls was analyzed and its correlation with clinical indicators was investigated. In vitro, we used tumor necrosis factor‐α to stimulate fibroblast‐like synoviocytes (FLS) of RA patients for cell based experiments. Subsequently, the overexpressed plasmid and small interfering RNA of LINC00638 were designed. Furthermore, we further analyzed the potential effects of LINC00638 on the proliferation and migration of RA‐FLS and the nuclear factor erythrocyte derived 2 related factor 2 (Nrf2)/heme oxygenase 1 (HO‐1) pathway. Results: LINC00638 expression was found to be significantly decreased in PBMCs of RA patients, and it was negatively correlated with erythrocyte sedimentation rate, interleukin (IL)‐17, reactive oxygen species (ROS), and disease activity scores for 28 joints (DAS28). Overexpression of LINC00638 activated the Nrf2/HO‐1 pathway, markedly decreased the expressions of IL‐6, IL‐17, IL‐23, ROS, as well as malondialdehyde, increased the total antioxidant capacity, and attenuated the proliferation and migration of RA‐FLS, while silencing of LINC00638 reversed these manifestations. Conclusions: LINC00638 was found to be expressed at low levels in RA patients and was associated with immune inflammation, oxidative stress, and disease activity. Overexpression of LINC00638 can reduce the proliferation as well as migration of RA‐FLS, and activate the Nrf2/HO‐1 pathway to inhibit the inflammation and oxidative stress. Abstract : LINC00638 is down‐expressed in fibroblast‐like synoviocytes from patients with rheumatoid arthritis. Overexpression of LINC00638 can inhibit cell proliferation and migration, on the contrary, knockdown of LINC00638 can promote cell proliferation and migration.